2017
DOI: 10.17116/terarkh20178912133-140
|View full text |Cite
|
Sign up to set email alerts
|

A fixed-dose lisinopril+amlodipine+rosuvastatin combination: prospects for its use in patients with hypertension and concomitant dyslipidemia

Abstract: In Russia, target blood pressure (BP) levels are achieved in only 14.4% of men and in 30.9% of women. The need for combination therapy of hypertension is as high as 70.7%. There are well-known benefits of combined antihypertensive therapy allowing for higher efficiency and better tolerability. One of the current combinations is a combination of an angiotensin-converting enzyme inhibitor and a calcium antagonist, which have pronounced protective activity and metabolic neutrality. Fixed-dose combinations have su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
2
0
5
Order By: Relevance
“…Rosuvastatin is a member of statins, which exerts their effects by blocking the HMG-CoA reductase enzyme in the liver. Studies have shown that rosuvastatin plays an important role in the treatment of hypercholesterolemia and hypertension [ 5 ]. Amlodipine is one of the dihydropyridine calcium channel antagonists and is commonly used in the treatment of hypertension with a satisfactory clinical effect.…”
Section: Introductionmentioning
confidence: 99%
“…Rosuvastatin is a member of statins, which exerts their effects by blocking the HMG-CoA reductase enzyme in the liver. Studies have shown that rosuvastatin plays an important role in the treatment of hypercholesterolemia and hypertension [ 5 ]. Amlodipine is one of the dihydropyridine calcium channel antagonists and is commonly used in the treatment of hypertension with a satisfactory clinical effect.…”
Section: Introductionmentioning
confidence: 99%
“…Больным АГ, СД 2 типа и ДЛП наряду с приемом эффективной комбинации иАПФ с антагонистом кальция, необходимо назначение гиполипидемической терапии, направленной на снижение частоты ССЗ и их ССО. Единственной фиксированной комбинацией иАПФ, антагониста кальция и статина в России является комбинация лизиноприла, амлодипина и розувастатина (препарат Эквамер, "Гедеон Рихтер", Венгрия), которая продемонстрировала свою эффективность в различных исследованиях [40,41]. Существуют несколько фиксированных комбинаций препарата Эквамер: лизиноприл 10 и 20 мг, амлодипин 5 и 10 мг, розувастатин 10 и 20 мг.…”
Section: современные принципы лечения аг и длп у пациентов с сдunclassified
“…Бόльшая польза комбинированной терапии по сравнению с монотерапией обусловлена рядом причин. Во-первых, отмечается рациональное фармакодинамическое действие за счет воздействия на различные звенья патогенеза АГ; во-вторых, сочетаются препараты с различными нежелательными эффектами, что может быть взаимно компенсировано за счет устранения контррегуляторных механизмов действия; в-третьих, обеспечивается максимальная органопротекция и, соответственно, уменьшение риска развития СС-осложнений; в-четвертых, использование нескольких препаратов в небольших дозах позволяет избежать развития дозозависимых нежелательных явлений [4]. Более того, комбинированная терапия помогает преодолеть инертность терапии, когда пациенты в течение длительного времени остаются на одном препарате, несмотря на неадекватный контроль АД [18].…”
Section:  монотерапия или комбинированная антигипертензивная терапияunclassified